MINISTRY OF HIGHER EDUCATION, SCIENCE AND INNOVATION OF THE REPUBLIC OF UZBEKISTAN FERGANA STATE UNIVERSITY - Azamjonova Azimakhon Avazjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: the article is devoted to the influence of mother tongue to the process of foreign language teaching, on the example of EFL. It also discloses the challenges, that teacher can face and proposals of overcoming them.